Exploring Barriers to the Consumption of Neglected and Underutilized Green Leafy Vegetables in Rural and Urban Populations of the Tribal Regions of Garo Hills, Meghalaya, India - , Sunanda Nongthombam; , Natasha R. Marak; , Chenxiang Rimchi N Marak; , Pavana Kumar; , Chingakham Basanti Devi; , Puspita Das (Archives of Current Research International, 2024)
Aim: To identify and analyze the barriers to the consumption of neglected and underutilized Green Leafy Vegetables (GLVs) in urban and rural settings of Garo Hills, Meghalaya, focusing on key determinants influencing consumption patterns. Study Design: Cross-sectional survey-based study. Place and Duration of Study: Urban and rural areas of Garo Hills, Meghalaya, conducted from January to May 2024. Methodology: A total of 90 respondents, 45 each from urban and rural areas, were surveyed using a structured questionnaire. The study assessed five key determinants: availability, perception of taste/flavor, knowledge of nutritional benefits, difficulty in preparation, and cost/affordability. Weighted averages were calculated to rank the barriers based on their perceived significance in each setting. Data were analyzed using descriptive statistics to identify differences in consumption patterns and barriers across the two settings. Results: Limited availability emerged as the most significant barrier for urban respondents, with a weighted average score of 7.5, highlighting poor access to GLVs in urban markets. In contrast, rural respondents identified a lack of knowledge about nutritional benefits as the primary barrier, scoring a weighted average of 13.2, indicating a critical need for awareness campaigns. Taste perception influenced consumption, ranking as the second-highest barrier in rural areas (4.7) and third in urban areas (5.6). Preparation difficulties were ranked second by urban respondents (5.7) and third by rural respondents (4.1). Cost and affordability were the least significant barriers in both settings, suggesting that financial constraints play a minor role compared to other factors. Conclusion: The study reveals significant differences in the barriers to GLV consumption in urban and rural Garo Hills. Addressing limited availability in urban areas and enhancing knowledge of nutritional benefits in rural areas are essential for improving GLV consumption. Tailored interventions are required to mitigate these barriers and promote the inclusion of GLVs in diets.